1990
DOI: 10.1165/ajrcmb/3.4.341
|View full text |Cite
|
Sign up to set email alerts
|

Junctional Adhesion Mechanisms in Airway Basal Cells

Abstract: The morphology of basal cells varies according to the height of the epithelium they are associated with. In taller epithelium, basal cells appear to have more tonofilaments (keratin filaments) than basal cells in shorter epithelium. We hypothesized that the changes in basal cell structure represent differentiation of junctional adhesion mechanisms related to the attachment strength necessary for the various-height epithelium. To evaluate this hypothesis, we used light- and electron-microscopic morphometry to q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…There has been some controversy as to whether basal cells are immature "precursors" of other bronchial epithelial cells or represent a differentiated population with specific functions [24]. The absence of cells expressing intermediate levels of 4-1BB is consistent with the later possibility and suggests that this antibody may be useful in isolating basal cells for functional studies.…”
Section: Discussionmentioning
confidence: 82%
“…There has been some controversy as to whether basal cells are immature "precursors" of other bronchial epithelial cells or represent a differentiated population with specific functions [24]. The absence of cells expressing intermediate levels of 4-1BB is consistent with the later possibility and suggests that this antibody may be useful in isolating basal cells for functional studies.…”
Section: Discussionmentioning
confidence: 82%
“…Because the sloughed cells were intact [1 I], it was concluded that cotton smoke affected their desmosome mechanisms for attachment, which is the primary mechanism for columnar cell adherence to the basal lamina in the sheep [13,14]. In unexposed regions of the trachea, all cells appeared normal, which indicates that the effect of smoke on tracheal cells is local and not systemic.…”
Section: Discussionmentioning
confidence: 99%
“…6,7,11). This close relationship suggests that a lesion in one component of the supracellular anchoring network may affect development of the whole network.…”
Section: Discussionmentioning
confidence: 93%
“…Collagen VII is found in the epithelial surface of the BMZ. Bar: 10 m. (6,7). In general, as the volume of the epithelium increases, the amount of junctional adhesion present in the supracellular anchoring network also increases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation